Analisis Keanekaragaman Isolat Bacillus thuringiensis yang Patogenik terhadap Serangga Hama Kubis (Crocidolomia binotalis) dengan Pendekatan Sistematika Numerik - Salaki, Christina L.; Situmorang, Jesmandt; Sembiring, Langkah; Handayani, Niken (Universitas Atma Jaya Yogyakarta, 2010)
Diversity of B. thuringiensis (Bt.) isolates pathogenic to C. binotalis was determined by using Numerical Systematic Method. Ten isolates were taken to represent 34 pathogenic isolates along with two reference strains namely B. thuringiensis serovar kurstaki and B. thuringiensis serovar israelensis. The test isolates were examined for 89 phenotypic characters by using convensional method for colonial and cell morphology (37 characters) as well as physiological characteristics (3 characters) but biochemical characterization (49 characters) was conducted by using commercial API-50 CHB procedures. All phenotypic characters existed in one of two mutually exclusive states and were either scored plus (1) of minus (0). The binary data were prepared in Programmer’s File Editor (PFE) software. The data then were analysed by using the Multi Variate statistical Package (MVSP) Plus-Version 3.1 using the Simple Matching Coefficient (SSM). Clustering was achieved using the UPGMA algorithm. The results were presented as dendrograms. It was obtained that the test isolates were clearly assigned to two distinct multimembered clusters defined by 79.6 similarity level (S-level) in the SSM, UPGMA analysis. The two distinct clusters represented by each of two widely known different group of Bt. strains, namely serovar israelensis and serovar kurstaki. The first cluster contained reference strain of B. thuringiensis serovar israelensis, and two of the isolates (Slk2.3, and YPPA1) and the second cluster contained another reference strain of B. thuringiensis serovar kurstaki, and 8 of the isolates. Therefore, it strongly suggested that the application of numerical-fenetic analysis could provide a tool to unravel the strain diversity belong to B. thuringiensis.